Short-term fasting decreases excitatory synaptic inputs to ventromedial tuberoinfundibular dopaminergic neurons and attenuates their activity in male mice. (3rd April 2018) - Kubota, Takafumi; Fukushima, Atsushi; Hagiwara, Hiroko; Kamiya, Yoshinori; Furuta, Miyako; Miyazaki, Tomoyuki; Fujioka, Hitomi; Fujiwara, Sei-Etsu; Funabashi, Toshiya; Akema, Tatsuo
Highlights: Whole-cell voltage-clamp techniques were applied to investigate TIDA neuron activity. Miniature excitatory postsynaptic currents in TIDA neurons were reduced by fasting. Fasting caused reduced cFos expression in TIDA neurons and increased serum PRL levels. Taken together, our results showed that fasting attenuated TIDA neuron activity. Abstract: Tuberoinfundibular dopaminergic (TIDA) neurons in the arcuate nucleus (ARC) of the hypothalamus play a role in inhibiting prolactin (PRL) secretion from the anterior pituitary. PRL is involved in a variety of behaviors, including feeding. Consequently, we hypothesized that fasting might reduce the activity of TIDA neurons, which might alter PRL secretion. However, direct examinations of TIDA neuron activity are difficult. Recently, transgenic mice were generated that expressed green fluorescent protein (GFP) under the control of the rat tyrosine hydroxylase gene. We first determined that GFP in the dorsomedial ARC was a reliable marker of TIDA neurons. Then, we performed electrophysiology and immunocytochemistry in GFP-labeled TIDA neurons to examine whether different feeding conditions could change their activity. Eight-week-old male mice were fed or fasted for 24 h. After sacrifice, we prepared acutely isolated brain slices for conducting whole-cell voltage-clamp recordings. TIDA neurons were identified with fluorescence microscopy. The mean amplitude of miniature excitatory postsynaptic currents (mEPSCs) was significantly reduced in fasting mice compared to fed mice, but different feeding conditions did not affect the mean mEPSC intervals. This result suggested that fasting reduced the number of excitatory synaptic inputs to TIDA neurons. To determine whether a reduction in excitatory synaptic inputs would cause a reduction in TIDA neuron activity, we examined the effect of 24-h fasting on c-Fos expression in the ARC. We found that fasting significantly reduced the number of Fos-positive TIDA neurons. In addition, serum PRL levels were significantly increased. Taken together, the present findings suggested that short-term fasting attenuated TIDA neuron activity.